PEMBATASAN HAK KHIYAR DALAM PERDAGANGAN SAHAM: ANALISIS TERHADAP KEBIJAKAN NON-CANCELLATION PERIOD BURSA EFEK INDONESIA - Abduh, Muhamad Rahmani; Akbar, Ilham; Ilmi, Fajrul; Pradana, Neco Erlin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the stock trading mechanism on the Indonesia Stock Exchange (IDX) and examine the Non-Cancellation Period policy from the perspective of Islamic law, particularly through the concept of khiyar. This research employs a normative legal method with a conceptual approach, focusing on the analysis of fiqh muamalah principles in relation to modern stock trading practices. The findings indicate that stock trading on the IDX is conducted through a structured electronic system, where transactions are deemed to occur upon the matching of buy and sell orders. The Non-Cancellation Period policy restricts the modification and cancellation of orders within a specific timeframe to maintain price stability and prevent potential market manipulation. From an Islamic law perspective, this restriction does not fundamentally contradict the concept of khiyar majlis, as orders that have not yet been matched cannot be considered legally binding contracts. Furthermore, based on the fiqh principles of dar’u al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ (preventing harm takes precedence over attaining benefit) and lā ḍarar wa lā ḍirār (no harm and no reciprocating harm), the policy can be justified as it aims to prevent collective harm and preserve market integrity. Therefore, the Non-Cancellation Period reflects an adaptation of Islamic legal principles within modern trading systems while maintaining justice and public interest